A Portable Molecularly Imprinted Sensor for On-Site and Wireless Environmental Bisphenol A Monitoring - Beduk, Tutku; Gomes, Matilde; De Oliveira Filho, José Ilton; Shetty, Saptami Suresh; Khushaim, Walaa; Garcia-Ramirez, Ricardo; Durmus, Ceren; Ait Lahcen, Abdellatif; Salama, Khaled Nabil (Frontiers in Chemistry, 2022)
The detection of pollutant traces in the public and environmental waters is essential for safety of the population. Bisphenol A (BPA) is a toxic chemical widely used for the production of food storage containers by plastic industries to increase the storage ability. However, the insertion of BPA in water medium leads to serious health risks. Therefore, the development of low-cost, practical, sensitive, and selective devices to monitor BPA levels on-site in environment is highly needed. Herein, for the first time we present a homemade portable potentiostat device integrated to a laser scribed graphene (LSG) sensor for BPA detection as a practical environmental pollutant monitoring tool. Recently, there has been an increasing need regarding the development of graphene based electrochemical transducers (e.g., electrodes) to obtain efficient biosensing platforms. LSG platform is combined with molecularly imprinted polymer (MIP) matrix. LSG electrodes were modified with gold nanostructures and PEDOT polymer electrodeposition to create a specific MIP biomimetic receptor for ultrasensitive BPA detection. The sensing device has the Bluetooth connection, wirelessly connected to a smartphone providing high sensitivity and sensitivity (LOD: 3.97 nM in a linear range of 0.01-10 µM) towards BPA. Two commercial bottled water samples, tap water, commercial milk and baby formula samples have been used to validate the reliability of the portable sensor device.